Psychrozymes as novel tools to biodegrade p-xylene and potential use for contaminated groundwater in the cold climate. (February 2021) - Miri, Saba; Davoodi, Seyyed Mohammadreza; Brar, Satinder Kaur; Rouissi, Tarek; Sheng, Yi; Martel, Richard
Graphical abstract: Highlights: Enzymatic biodegradation of p-xylene (monoaromatic hydrocarbon model) was studied. Psychrozymes can be used for the rapid biodegradation in cold climate regions. Xylene monooxygenase and catechol 2, 3-dioxygenase have a matching end product. Cold-active enzymes have unique thermodynamic and kinetic behavior. The enzymes cocktail degraded 200 mg/l of p-xylene within 48 h at 15 °C. Abstract: Sites contaminated by petroleum hydrocarbons in cold-climate regions have recently received significant attention due to their sensitive ecosystem and human health impacts. Two cold-adapted pseudomonas strains were isolated from contaminated groundwater and soil. As xylene monooxygenase from Pseudomonas synxantha S2TR-26 and catechol 2, 3-dioxygenase from Pseudomonas mandelii S2TR-08, have a matching end product, they acted in symphony to degrade p-xylene. Their unique thermodynamic and kinetic behavior permits them to achieve rapid degradation of p-xylene at low temperatures (<15 °C). The results showed that the sequential action led to the conversion of 200 mg/l of p-xylene within 72 h and complete degradation after 120 h. The cocktail of these enzymes with a ratio of 1:1.5 (xylene monooxygenase: catechol 2, 3-dioxygenase) confirmed the complete degradation of p-xylene within 48 h at 15 °C. This approach will allow efficient biodegradation of p-xylene to minimize the bioremediation duration in cold-climate regions.